2007
DOI: 10.1097/01.cej.0000220642.54094.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aloe vera leaf pulp extract on Ehrlich ascites tumours in mice

Abstract: Among the various known therapeutic effects of Aloe vera (L.) Burm. fil., a few recent studies have shown that preparations of the plant leaves can prevent or regress the growth of certain tumours. In this study, undertaken with A. vera leaf pulp extract against Ehrlich ascites tumours in mice, the animals were separated into five groups: I - healthy control, II - tumour control, III - experiment 1 (extract given before tumour inoculation), IV - experiment 2 (extract given with tumour inoculation) and V - expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
0
19
0
3
Order By: Relevance
“…Yaprakların yaralanması veya parçalanması durumunda yapışkan jelimsi bir sıvı yayılır. Cilt hastalıklarında özellikle bu sıvı etkili olarak kullanılmaktadır (21).…”
unclassified
“…Yaprakların yaralanması veya parçalanması durumunda yapışkan jelimsi bir sıvı yayılır. Cilt hastalıklarında özellikle bu sıvı etkili olarak kullanılmaktadır (21).…”
unclassified
“…Akev et al (93) reported that the main lectin of the Aloe vera gel, aloctin 1, has the ability to prevent tumour development in mice; probably by activating the immune system. Lectin-like substances from the leaves of Aloe vera and Aloe saponaria have haemoagglutinating properties and are able to promote the growth of normal human cells in culture but inhibit tumour cell growth (94,95).…”
Section: Woundsmentioning
confidence: 99%
“…At a concentration of 10 µM, aloe-emodin exhibits antiproliferative activity against the Merkel carcinoma cell line, which is an aggressive and rare type of sun-induced skin tumor that primarily affects elderly individuals (Wasserman et al, 2002). Aloctin I, a type of lectin isolated from the leaves of the A. vera plant, prevents tumor growth in mice when administered prior to tumor implantation (Akev et al, 2007).…”
Section: Aloe Arborescens Mill Xanthorrhoeaceaementioning
confidence: 99%